Pengaruh Intellectual Capital Dan Islamic Performance Index Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Bank Umum Syariah Periode 2019-2024 - Shiffa Mutiara Aliyyah; M. Iqbal; Aziz Septiatin (Journal of Economics and Business, 2026)
This study aims to analyze the influence of Intellectual Capital and Islamic Performance Index on Company Value with Financial Performance as an Intervening variable in Islamic Commercial Banks in Indonesia during the period 2019 to 2024. Intellectual Capital is an intangible asset owned, while the Islamic Performance Index is used to measure Company Performance based on Sharia principles. Company Value is an important indicator that reflects investor perceptions of the Company's prospects in the future. This type of research is quantitative with secondary data derived from annual financial reports published by the Financial Services Authority (OJK) and each bank. The sample in this study was selected using purposive sampling, resulting in 7 banks that met the criteria in the study. The data obtained were then processed using the Eviwes Student 12 application.The results of the study show that IC consisting of VACA, VAHU, and STVA has no effect on Financial Performance, and IPI consisting of EDR has no effect, and PSR has an effect on Financial Performance. IC consisting of VACA and VAHU has an effect on Company Value, STVA has no effect, and IPI consisting of EDR has no effect, and PSR has an effect on Company Value